Mindful, Meaningful, And Joyful Approaches: Challenges And Potential Solutions As Perceived By EFL Teacher At Primary School Level - Yazid Mubarok; Dwika Herdiawan, Rama; Nurhidayat, Eka (Papanda Publisher, 2024)
This research explores English as a Foreign Language (EFL) teachers’ perceptions, implementation practices, challenges, and strategies in applying the Mindful, Meaningful, and Joyful (MMJ) approach at an Islamic primary school in Indonesia. This research adopts a qualitative case study design, using open-ended questionnaires and semi-structured interviews with three EFL teachers as primary data sources. This research applies Braun and Clarke’s (2006) thematic analysis to identify patterns related to teacher perceptions, classroom implementation, and contextual constraints. This research reveals that teachers perceive MMJ as a holistic and student-centered approach rather than a set of isolated techniques. This research finds that teachers implement MMJ through reflective routines, culturally relevant stories, joyful projects, and mindfulness practices that promote emotional engagement and language acquisition. This research also identifies major challenges, including limited instructional time, resource constraints, student diversity, and sociocultural expectations. This research shows that teachers respond to these challenges with adaptive strategies, such as integrating MMJ into the national curriculum, simplifying tasks, and using local cultural elements to sustain student motivation. This research highlights the evolving role of teachers as emotional caregivers, learning designers, and reflective practitioners, emphasizing the importance of teacher agency in educational innovation. This research concludes that the MMJ approach, when supported by professional development and contextual flexibility, holds significant potential for enriching English language teaching in Indonesian primary schools.